Water place names in the pre-Latin ligurian context. A study in prehistoric toponomastics and semantics - Perono Cacciafoco, Francesco (2015)
This paper outlines a new applied epistemological aspect of the so-called Convergence Theory that is aimed to develop a potentially "homogeneous" vision between the different approaches in the field of Indo-European linguistics. This work tries to reconstruct an Italian and European toponymic area characterized by place names linked to the root *alb-, with a delineation of the "semantic steps" produced, over the centuries, by the same root, following a potential all-embracing approach. It seems that paleo-Ligurian place names of the type Alba, Old European river names Albis and the like, as well as their ablauting forms Olb- (> Orb- in Romance Ligurian), do not directly reflect the proto-Indo-European adjective *albho- 'white'; but rather they all seem to continue a pre-proto-Indo-European extended root *Hal-bh- 'water', cognate with the Sumerian ḫalbia (> Akkadian ḫalpium 'spring', 'well', 'water mass', 'water hole'). A further analysis of this *Hal-bh-, moreover, leads to a comparison with the proto-Indo-European root *Hal- 'nourish'. The proto-Indo-European suffixed form *HwaH-r- 'water', then, demonstrates a similar diffusion.